Vegetation diversity, composition and structure in a cattle agro-landscape of Matiguás, Nicaragua. - Sánchez Merlos, Dalia (2005)
The diversity, composition and structure of vegetation in a cattle landscape in Matiguás, Nicaragua was characterized, and the floristic and structural differences of six types of habitats (secondary forests, riparian forests, charrales, live fences and pastures with high and low tree cover) were compared. A total of 3 949 trees of 180 species and 52 families were recorded. Forty six percent of the total trees reported for the landscape were represented by Guazuma ulmifolia (18.5%), Bursera simaruba (13.2%), Tabebuia rosea (6.3%), Enterolobium cyclocarpum (4.2%) and Albizia saman (3.4%). Many of the dominant species in the landscape were typical of open and disturbed areas. There were significant differences between the different habitats in the patterns of tree species richness, abundance, diversity, structure and floristic composition. The riparian forests had greater tree richness (p=0.0001) and diversity (p=0.0009) than other habitats. The floristic composition varied across habitats, with pairs of habitats sharing between 18.4 and 51.6% of the same tree species, and with clear differences in composition between the forested (riparian and secondary forests) and agricultural habitats. Of the habitats studied, the riparian forests and secondary forests seem to have greatest value for the conservation of the flora in the agropaisaje because they have the greatest species richness, and maintain small populations of endangered species. On the basis of the study, we recommend including agricultural landscapes in strategies to conserve tree diversity and suggest measures to ensure the maintenance of tree diversity in the Matiguas landscape